The social shaping of nuclear energy technology in South Africa - Britta Rennkamp; Radhika Bhuyan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper analyses the question why the South African government intends to procure nuclear energy technology, despite affordable and accessible fossil and renewable energy alternatives. We analyse the social shaping of nuclear energy technology based on the statements of political actors in the public media. We combine a discourse network analysis with qualitative analysis to establish the coalitions in support and opposition of the programme. The central arguments in the debate are cost, safety, job creation, the appropriateness of nuclear energy, emissions reductions, transparency, risks for corruption, and geopolitical influences. The analysis concludes that the nuclear programme is not primarily about generating electricity, as it creates tangible benefits for the coalition of supporters.
Keywords: O14; Q48; O33; O55; 330; nuclear energy; energy policy; science and technology policy; discourse network analysis; South Africa